Retro Thrift Sdn Bhd / Nur Farah Diyana Muhamad - Nur Farah Diyana, Muhamad (2020)
Retro Thrift Sdn Bhd is a form of business based on partnership which consists of 4 members that hold and play a big role in running the business. The roles include the General Manager, Marketing Manager, Administrative Manager and Financial Manager. Our business is located at Lot 1, Ground Floor, Dewan Sri Iskandar, Jalan Setiawangsa 13, Taman Setiawangsa, 54200 Kuala Lumpur. Retro Thrift is a company which focuses on the sale of used times in Malaysia. We offer various kind of used items including women’s clothing, men’s clothing, children’s clothing, accessories, children toys and home appliances all in a store. These items are sold with guaranteed low price as our target is the young adults and community with middle or low incomes. Also, those fashion lovers in the community that would like to vary the collection in their closets. We are determined that our business will become huge in the future and known across Malaysia. To ensure that our customers will be loyal to our sore and becomes the attention in the community, we decided to import various used items from the overseas especially for women’s and men’s clothing. This is because the quality for the imported items are higher and the variations of the items are very satisfying. We will frequently restock new items every week to maximize the satisfaction of our customers and also to t=attract more new customers to our store. Our store also offers online shopping for those with no transportation or too lazy to walk into our store. This will ensure the convenience of the customers by these two options which either walk in shopping or online shopping. With the loan provided by the bank, we hoped that our business will be able to achieve an outstanding demand from the customers. Our business is expected to commence on the 1st January 2021 with the vision of ensuring that our business would be known, established and fulfilled the needs and wants of our customers. These can be realized by the strong efforts and full cooperation by each of the partners contributions to the business. Thrifts has the potential of being a profitable business only if it is done and managed systematically. This will secure a long run business with stable profits made.